EFEKTIVITAS PENGENDALIAN INTERNAL PEMBERIAN KREDIT STUDI KASUS PADA PT. BANK BRI (PERSERO) TBK UNIT DAENG SIRUA MAKASSAR - Ansyarif Khalid; Sitti Zulaeha; kisrawati asjudalastri (INVOICE : JURNAL ILMU AKUNTANSI, 2019)
Internal control is, a system of procedures that can automatically check each other recording between parts or functions within an organization and prioritize accuracy and administrative. Usually this is done by employing two or more people independently, to obtain the same numer or the same result. Granting of credit, is a general procedure of credit regarding the terms, conditions or guidance of actions to e performed since the sumission of credit application by the customer until the paying off a credit y the bank.The title of this research is: Effectiveness of internal control of lending (case study at PT Bank BRI Daeng Sirua Makassar).As for the problem studied by the author is whether the internal control of credit extended by Bank BRI (Persero) Tbk Unit Daeng Sirua has been effective.This research uses descriptive qualitative with case study approach, with carat question and answer. The conclusion is obtained from the result of study, the effectiveness of internal control of the grant held by PT. Bank BRI Daeng Sirua Makassar in supporting the procedure of credit provision is quite effictive.